2018
DOI: 10.1177/0013124518781911
|View full text |Cite
|
Sign up to set email alerts
|

Causes of Challenging Behavior in Primary Schools: The Perspectives of Students in Phoenix, South Africa

Abstract: Students’ challenging behavior has become a serious problem internationally. In South Africa, there are reports highlighting that even primary schools experience serious forms of challenging behavior by students. This article emanates from a case study that utilized the social cognitive theory to understand how primary schools address this phenomenon. To get students’ perspectives of what causes them to exhibit challenging behavior, a purposive sample of nine students ( N = 9) from three primary schools was id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 10 publications
(29 reference statements)
0
5
0
Order By: Relevance
“…This research revealed a variety of causes of student challenging behavior. Contrary to the student’s perspectives which revealed that more school factors than home factors caused them to exhibit challenging behavior in school (Rubbi Nunan & Ntombela, 2018), the teacher’s perspectives reveal that there are more home and social factors than school factors which cause students to exhibit challenging behavior in school. This article highlights how negative family dynamics, unfulfilled needs, exposure to social ills, and a lack of support influence student behaviors and make them vulnerable.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…This research revealed a variety of causes of student challenging behavior. Contrary to the student’s perspectives which revealed that more school factors than home factors caused them to exhibit challenging behavior in school (Rubbi Nunan & Ntombela, 2018), the teacher’s perspectives reveal that there are more home and social factors than school factors which cause students to exhibit challenging behavior in school. This article highlights how negative family dynamics, unfulfilled needs, exposure to social ills, and a lack of support influence student behaviors and make them vulnerable.…”
Section: Discussionmentioning
confidence: 74%
“…A study by Rubbi Nunan and Ntombela (2018) on primary school students’ perspectives of what causes them to exhibit challenging behavior in school revealed that more school factors than home factors influenced their behaviors, and that teachers need to understand the causative factors of student behaviors. Following their study, this research seeks to probe and accentuate primary school teachers’ perspectives of what causes students to exhibit challenging behavior in school to provide an outlook for understanding students first, before addressing their behavior in schools, thus the aim of this article.…”
Section: Introductionmentioning
confidence: 99%
“…It raises concerns about the social dynamics under which they develop within and outside the school system, what behaviors are they exposed to at home, in their communities and schools, and how do these behaviors shape their perceptions of what is acceptable and non-acceptable behavior? Rubbi Nunan and Ntombela (2018) also question the prevailing culture in some schools where students feel oppressed, undervalued, and unaccepted. Such feelings could promote displays of challenging behavior as students seek attention and acceptance.…”
Section: Discussionmentioning
confidence: 99%
“…Students’ challenging behavior has been a consistent problem over time and in different countries (Crawshaw, 2015), reportedly disrupting the teaching and learning process in schools (Kuronja et al, 2019; Rubbi Nunan & Ntombela, 2018). In South African primary schools, challenging behavior has escalated to such an extent that it is becoming very difficult for teachers to perform their daily duties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation